EFL teachers' perceptions and practices of reflective teaching as a tool to professional development : - Nguyễn, Thị Hà (Trường đại học Cần Thơ, 2019)
The main purpose of this study is to indicate (1) EFL teachers’ perceptions of the roles of reflective teaching for their professional development, and (2) their practices of reflective teaching for their professional development. From the findings of this study, some implications for teacher training courses will be evident